Correlation of Salmonella enterica and Listeria monocytogenes in Irrigation Water to Environmental Factors, Fecal Indicators, and Bacterial Communities - Gu, Ganyu; Strawn, Laura K.; Ottesen, Andrea R.; Ramachandran, Padmini; Reed, Elizabeth A.; Zheng, Jie; Boyer, Renee R.; Rideout, Steven L. (Frontiers in Microbiology, 2021)
Outbreaks of foodborne illnesses linked to fresh fruits and vegetables have been key drivers behind a wide breadth of research aiming to fill data gaps in our understanding of the total ecology of agricultural water sources such as ponds and wells and the relationship of this ecology to foodborne pathogens such as Salmonella enterica and Listeria monocytogenes. Both S. enterica and L. monocytogenes can persist in irrigation water and have been linked to produce contamination events. Data describing the abundance of these organisms in specific agricultural water sources is valuable to guide water treatment measures. Here, we profiled the culture independent water microbiota of four farm ponds and wells correlated with microbiological recovery of S. enterica, L. monocytogenes and fecal indicator testing. Correlation between abiotic factors, including water parameters (temperature, pH, conductivity, dissolved oxygen percentage, oxidation reduction potential, and turbidity) and weather (temperature and rainfall), and foodborne pathogens were also evaluated. Although abiotic factors did not correlate with recovery of Salmonella or Listeria, fecal indicators were positively correlated with incidence of Salmonella in well water. Bacterial taxa such as Sphingomonadaceae and Hymenobacter were positively correlated with the prevalence and population of Salmonella, and recovery of L. monocytogenes was positively correlated with the abundance of Rhizobacter and Comamonadaceae. These data will support evolving mitigation strategies to reduce the risk of produce contamination by foodborne pathogens through irrigation.